Entrepreneurial Mindset and Neuroscience: The Role of Electroencephalography in Measuring Risk-taking, Creativity, and Decision-Making - Silitonga, Lusia Maryani; Dharmawan, Budi; Murti, Astrid Tiara (Universitas Pendidikan Ganesha, 2025)
Entrepreneurial skills such as risk-taking, creativity, and decision-making are critical for fostering innovation and business success. This study examined the correlation between electroencephalography (EEG)-measured attention levels and entrepreneurial skills among university students in Indonesia. Using a one-group pretest-posttest experimental design, data were collected through EEG recordings, pretests, posttests, surveys, and semi-structured interviews over five class meetings. The NeuroSky MindWave Mobile EEG headset was used to monitor students' real-time attention levels, while their learning engagement and satisfaction were assessed through validated Likert-scale questionnaires. The results revealed a significant positive correlation between EEG-measured attention and creativity, with students showing notable improvements in risk-taking and decision-making skills after EEG-monitored learning activities. Engagement was strongly linked to satisfaction, suggesting that EEG feedback enhanced students’ focus and motivation. Interview findings further confirmed that real-time EEG visual feedback helped students regulate their attention and optimize learning. These results demonstrate the potential of EEG technology in entrepreneurship education, providing objective cognitive engagement insights. Future research should explore EEG applications in diverse educational contexts with larger sample sizes to validate its impact.